Bioassay on n-Hexane Extract of Leaves Cassia alata against Candida albicans - Muhammad Bahi; Radilla Mutia; Mustanir Mustanir; Endang Lukitaningsih (Universitas Syiah Kuala, 2014)
The study of biological activity from n-hexane extract of leaves’ Cassia alata had been done against Candida albicans as bioindicator. Dried leaves of C. alata (850 g) were macerated into n-hexane to obtain a dark green crude extract (31.79 g). The n-hexane crude extract was then subjected to vacuum liquid chromatography (VLC) and eluted with n-hexane and ethyl acetate to give 4 sub-fractions, namely fraction A (7.7251 g), fraction B (1.9419 g), fraction C (1.3565 g) and fraction D (1.4737 g) respectively. Based on phytochemical analysis, both nhexane crude extract and chromatographic sub-fractions contained steroids as their secondary metabolite constituent. The antifungal activity was tested against C. albicans using the agar-disc diffusion method with three different concentrations (10, 30 and 50%). Fraction D showed medium antifungal activity at 10.6, 11.3 and 12.6 of diameter-inhibition zones (mm) respectively.